Guyana - Carpenter, Allan, 1917-2003.; Balow, Tom (Chicago: Childrens Press, 1970)
An introduction to the geography, people, history, resources, and attractions of the small South American country which gained independence from Britain in 1966.
NLJCols20082021
Keywords: Guyana -- Juvenile literature; Guyana; Guyana; Juvenile works